Verbal aggressiveness and argumentativeness at the primary school: A gender-specific analysis - Bardas, Dimitrios; Litsa, Maria; Bekiari, Alexandra; Hasanagas, Nikolaos (American Journal of Education and Learning, 2024)
The study examined the effects of verbal aggressiveness and argumentativeness in relation to gender. Two experimental groups (44 children-18 boys and 26 girls-for the study of verbal aggressiveness and 61 children-29 boys and 32 girls-for the study of argumentativeness) and a control group (29 children-17 boys and 12 girls) in three primary schools in Magnesia participated. A questionnaire was used before and after an intervention. Results: Verbal aggression had a stronger influence on boys than arguementativeness on girls. Regarding the variable “badly threateningly,” the influence for boys was statistically significant in the control group after relaxation time, with more participation for the male physical education instructor. Regarding the variable “badly threateningly,” the influence for girls was statistically significant in argumentativeness before and after the speech, with more participation for the male physical education instructor after the speech. Concerning the variable “came back,” the influence for boys was statistically significant in verbal aggressiveness before and after the speech, with more participation for the female physical education instructor after the speech and for the control group for girls before relaxation time that came before the female and young physical education instructor. The variable of “how much aggressive” showed that the influence for boys was statistically significant in verbal aggressiveness before the speech with more participation in young physical education instructors. Two experimental groups may be more beneficial in the early and terminal stages of learning for these two dependent variables.